Bioinspired multiscale Al2O3-rGO/Al laminated composites with superior mechanical properties. (15th July 2021) - Zhang, Zhiming; Fan, Genlian; Tan, Zhanqiu; Zhao, Haitao; Xu, Yanjin; Xiong, Dingbang; Li, Zhiqiang
Abstract: Nacre's multiscale reinforcing mechanisms provide lessons for the design and fabrication of high-performance engineering composites. In this study, the addition of hierarchically aligned flake Al2 O3 and reduced Graphene Oxide (rGO) nanosheets into Al matrix constitute the bioinspired multiscale Al2 O3 -rGO/Al laminated composite via flake powder metallurgy. The results show that multiscale Al2 O3 -rGO reinforcements have the synergistic strengthening effect of 1 + 1>2. Extra strengthening mechanism is attributed to enhanced load transfer due to good bonding at Al2 O3 /rGO/Al interface. Compared to Al2 O3 /Al composite, the uniform elongation of Al2 O3 -rGO/Al laminated composite doesn't decrease due to the higher strain hardening capacity. The work presented here provides a new strategy for developing advanced composites with simultaneous enhancement of the modulus-strength-ductility.